Gamification: when pedagogical innovations benefit internship seekers - Santos - Guevara, Brenda N.; Rincon - Flores, Elvira G. (Proceedings of the International Conference on Education, 2020)
Results in higher education and literature have shown that gamification favors intrinsic motivation, cognitive process, and the social aspects of learning by engaging students with their courses. We present the use of a Leaderboard, integrating the used award system, built with eleven nicknames, six avatars, and seven types of badges. The course Growth-related Competencies aims to prepare students for the search of their internships through tools that allow them to develop professional competencies. Due to recruitment process preparation is usually exhaustive, this study points to examine whether this gamification system engaged students with course content. The impact in their course performance was the point of study as a result of the improvement done to this gamification design while students review all the recruitment process, built their curriculum vitae, have a mock interview and familiarize with job boards, mainly. We found, through exploratory qualitative research, that students chose an avatar or nickname (optional for students) according to something meaningful for them such as a role model they have or a character with whom they share characteristics in their own opinion. We also learned they found their motivation to participate in gamification as an opportunity to get recognition from teachers and classmates, as well as a reaffirmation of their performance while developing their professional competencies and get prepare to search for their internships. Personal satisfaction, extra points and rewarding were also reasons for them to participate as members of the Leaderboard of the course.